2007
DOI: 10.1177/039463200702000304
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Biphosphonates in Dental Surgical Implants

Abstract: Biphosphonates are largely used for their unquestionable properties of inhibiting bone resorption by osteoclasts in the treatment of various osteometabolic illnesses such as osteoporosis, multiple myeloma, tumors which metastasize to the bone and malignant hypercalcemia. In this literature review the physico-chemical properties, biologic activities and the mechanisms of action of biphosphonates are described. The use of these drugs is discussed, analyzing the quantity of results which have emerged through in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…The study included 15 rabbit calvaria bone defects. Four defect groups were created in each rabbit calvaria: ( 1 ) untreated bone defect; ( 2 ) PLGA only; ( 3 ) 2 mg of pamidronate with PLGA; and ( 4 ) 3 mg of pamidronate with PLGA. In radiographic analysis, radiopacity was lower in pamidronate groups at 1, 2, 4, 6 and 8 weeks after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study included 15 rabbit calvaria bone defects. Four defect groups were created in each rabbit calvaria: ( 1 ) untreated bone defect; ( 2 ) PLGA only; ( 3 ) 2 mg of pamidronate with PLGA; and ( 4 ) 3 mg of pamidronate with PLGA. In radiographic analysis, radiopacity was lower in pamidronate groups at 1, 2, 4, 6 and 8 weeks after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Non-amino-bisphosphonates, such as clodronate and etidronate, inhibit bone resorption primarily by inducing osteoclast apoptosis through the formation of intracellular metabolites in osteoclasts. Amino-bisphosphonates, such as pamidronate, alendronate or zoledronate, offer greater potency through the addition of a primary amino-nitrogenated base (-NH2) ( 3 , 4 ). These act by inhibiting farnesyl diphosphate (FPP) synthase, a key enzyme in the mevalonate pathway ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The theory behind this positive effect is that once bisphosphonates are released from the surface of the coated implant, there is a localized reduction in osteoclastic activity, altering the balance of bone remodeling in favour of increased osteoblastic activity, leading to increased bone formation which in turn increases the local bone density [197,198]. The authors hope that this improved early fixation may reduce the rate of late implant failures and could also allow earlier loading times.…”
Section: Positive Effects Of Bisphosphonates On Dental Implant Treatmentmentioning
confidence: 99%
“…The estimated prevalence of BRONJ in patients treated with oral bisphosphonates was 0.89% [70]. Furthermore, recent studies used oral bisphosphonates to assess the osteointegration of dental implants; some authors reported that clodronate could be useful in the maintenance of primary stability [71][72][73]. Zuffetti, et al administred a 3% clodronate solution mixed with a surfactant (Tween-20) at a 1:3 ratio both at the implant surface and at the implant site, reporting that oral BPs may positively affect implant survival in the preloading and postloading phases in partially and fully edentulous patients [74].…”
mentioning
confidence: 99%